Compulsive immobility: Understanding the role of health on collective efficacy - Blake W. Powell; Stephen F. Ostertag; Xiaojin Chen (Elsevier, 2022)
Most health care approaches to understanding social ills are rooted in strain or ecological models. Strain models assume that the impact of poor physical health operates through the individual, that it is the individual suffering from poor health who engages in social ills as a means of adapting, and that the impact of poor health is rather direct and immediate. Meanwhile, ecological approaches of health acknowledge how poor health may impact others and the collective, but poorly account for the case in which this is not so, leaving unexplained the many instances of people who are in poor health but remain actively engaged with their communities and preserve relationships that nurture trust, shared norms, and cooperation. To rectify this problem, we introduce the concept of "compulsive immobility": the situation in which those in poor health are compelled to stay indoors and refrain from community socialization. We argue that compulsive immobility mediates the relationship between poor physical health and collective efficacy, suggesting that illness, specifically to a point of physical immobility (e.g., bedridden), enables poor health to detract from collective efficacy. This allows scholars to both acknowledge how poor health may impact the individual and community, while specifying the mechanism through which it operates. To support our claim, we draw on GSS data to examine the relationship among poor health, health-related immobility, and collective efficacy. Our results provide empirical support for our argument, revealing that general health conditions influenced the level of generalized trust directly and indirectly through compulsive immobility. We conclude with suggestions on how compulsive immobility might impact neighborhood crime and propose ways through which subsequent research may refine and further test compulsive immobility as a mediator between poor health and collective efficacy.